國小低年級跨領域素養導向美感教學之課程實踐 -以身高樹為例 The Curriculum Practice of Cross Domain Competence Oriented Aesthetic Education -Taking Height Measurement on the Tree - 高月蓮 Yueh-Lien Kao; 鄭淵全 Yuan-Chuan Cheng (National Changhua University of Education, 2024)
本研究在探究國小低年級跨領域素養導向美感課程「身高樹」之實施歷程、困境、解決策略及實施成效。研究者以翰林版國小二級國語教材結合自編美感課程教材做為跨領域美感課程，以 TSING 國小 2 年級學生為對象，進行為期 6 個月的課程實踐，將課程設計理念及實踐經驗視為作品，辨析其美感性質。透過學生學習檔案、課程觀察紀錄、回饋單、省思札記、跨領域美感教學課程檢核表等，取得質性研究資料，進行分析與討論。本研究主要發現如下：一、以跨域統整架構情境化的課程，透過滾動式修正，可發展素養導向美感課程。二、跨領域素養導向教學美感課程發展時可透過教師營造生活美感體驗機會、小組合作、正向鼓勵、典範學習等進行有機整合，解決教學時數問題。三、跨領域素養導向美感課程「身高樹」，利用校園空間營造美學教育，探索體驗，增加學生對環境美的感知能力，能有效提升低年級學生學習興趣及成效。四、參與專業社群、增能研習等歷程，透過社群專業對話，認識核心素養，並進行課程實踐歷程探究，建立分享機制，與夥伴共同進行教學改良與精進，亦可促進教師專業成長。 This study investigates the implementation process, challenges, solutions, and impacts of the "Height Measurement on The Tree," a cross-disciplinary and competency-oriented aesthetic program designed for junior elementary school students. The researcher designed this cross-disciplinary aesthetic course by integrating the Hanlin version of the second-grade Chinese textbook with a self-compiled aesthetic course textbook and conducted a six-month teaching session with a group of second-grade Tsing primary school students. This study examines their aesthetic nature by treating the course design and practical experience as works of art. Qualitative research data were collected from students' learning files, class observation records, feedback sheets, reflection notes, and cross-disciplinary aesthetic teaching curriculum checklists. Based on the analysis and discussion of the data, this study reaches the following conclusions: 1. A cross-disciplinary, contextually adapted course framework with iterative corrections can facilitate the development of cross-disciplinary and competency-oriented aesthetic courses. 2. The issue of limited teaching hours can be addressed through the organic integration of courses, which includes creating an aesthetic experience of life, fostering group collaboration, providing positive reinforcement, and promoting model-based learning. 3. Participation in the "Height Measurement on The Tree," a cross-disciplinary and competency-oriented aesthetic program, significantly enhances junior students' learning interest and improves learning outcomes 4. Teachers can advance their professional growth by engaging in professional communities and participating in enhanced programs. Effective course design can overcome the limitations related to scheduling and disciplinary constraints, aligning with actual learning contexts. Teachers can learn to integrate multimedia into their teaching by strengthening their expertise in art. By exploring the teaching process and establishing mechanisms for sharing, more educators can recognize the potential of a new curriculum. Administrators should consider a broader range of feedback to improve the curriculum.